Development of Ethnoscience-Based Critical Thinking Instrument in Physics Learning - Ilwandri Ilwandri; Festiyed Festiyed; Tomi Apra Santosa (Universitas Muhammadiyah Enrekang, 2023)
This study aims to find out to produce a valid and reliable Project Based Learning integrated ethnoscience instrument in Newton's Law material. This type of research is a development research with 4D model. The research sample came from 2 physics education lecturers and physics teachers of SMA Negeri 4 Kerinci. Data collection techniques come from observation, interviews and validation questionnaires. The instrument in this study was a validation sheet using a likers scale. Data analysis is qualitative and quantitative analysis techniques with the help of the SPSS version 21 application. The results show the average validation value of ethnoscience instruments of 0.710 with very valid criteria and a reliability value of 0.845 high criteria. This finding explains that the ethnoscience instrument integrated with project-based learning is very feasible to be developed in learning physics material on Newton's Law